Evaluation of Pedestrians' Gaze Behavior When Crossing the Road Using Eye-Tracking Technology: Implications for Autonomous Vehicle Led Communication Interface - Zhanguzhinova, Symbat; Mako, Emese (Communications - Scientific Letters of the University of Zilina, 2024)
Since autonomous vehicles (AV) are in the testing process, it is an open question of how pedestrians will communicate with self-driving cars. Nowadays, explicit communication pattern is the main way of pedestrian-driver interaction, however, AV may use implicit communication when making crossing decisions. This study aims to analyze pedestrians' gaze behavior when crossing the road using an eye camera and find the most applicable location for the LED interface on AVs. 10 pedestrian crossings in Gyor, Hungary were analyzed using the synchronized eye-tracking (ET) technology and regular video cameras for combined data processing. The data were analyzed using digital image processing techniques and statistical methods to identify where pedestrians looked and whether a pedestrian-driver interaction was captured during the crossing maneuver.
Keywords: AV; LED interface; pedestrian; eye-tracking; gaze behavior